Challenges in the Implementation of Good Governance in the Administration of Residents with Disabilities in Badung Regency - Juniarta Dameria; Ni Wayan Widhiasthini (Green Publisher Indonesia, 2025)
This study aims to analyze the challenges in implementing good governance in the management of the administration of people with disabilities at the Population and Civil Registration Office in Badung Regency. Badung Regency was chosen because it has the highest regional revenue in BaliProvince and a significant population of people with disabilities. The research employs a qualitative approach. Data were collected through interviews, observations, and analysis of official documents. Informants were selected through purposive sampling, involving 10 individuals from government officials and people with disabilities. The results show that the Population and Civil Registration Office in Badung Regency has implemented various inclusive initiatives, such as mobile administrative services and accessibility facilities. However, the effectiveness of these services is still hindered by limitations in human resources and uneven socialization (sosialisasi). The five main challenges in implementing good governance are limited human resource capacity, uneven socialization, weak supervision mechanisms, communication barriers, and inadequate physical accessibility. The impact of exemplary governance implementation is seen in increased service accessibility and strengthened rights for people with disabilities, although these impacts are not evenly distributed geographically. It is concluded that implementing good governance has brought significant progress, but greater efforts are still needed to achieve truly inclusive and equitable services. Research recommendations include enhancing human resource capacity, strengthening socialization, and improving physical accessibility to enhance the quality of administrative services for people with disabilities in Badung Regency.